83.3k views
13 votes
The value of polynomial 5x-4x^2+3, when x=-1


2 Answers

10 votes

Answer:

-6

Explanation:


\text{Given that,}\\\\5x-4x^2 +3 \\\\\text{When}~ x = -1,\\\\~~~5(-1) -4(-1)^2 +3 \\\\=-5-4(1)+3\\\\=-5-4+3\\\\=-5-1\\\\=-6

User Zhe
by
5.0k points
1 vote


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \huge\underline\mathfrak{\color{fuchsia} {AnSwer}}


\: \: \: \: \: \: \: \: \: \: \:


\tt{p(x)=5x-4x^2 + 3}


\: \: \: \: \: \: \: \: \: \: \:

On putting x= -1


\: \: \: \: \: \: \: \: \: \: \:


\: \: \: \: \: \: \: \: \: \tt{p(-1)=5(-1)-4(-1)2+ 3}


\: \: \: \: \: \: \: \: \: \: \:


\: \: \: \: \: \: \: \: \:\tt{p(-1)=-5-4(1) +3}


\: \: \: \: \: \: \: \: \: \: \:


\: \: \: \: \: \: \: \: \:\tt{p(-1)=-5-4+3}


\: \: \: \: \: \: \: \: \: \: \:


\: \: \: \: \: \: \: \: \:\tt{p(-1)=-9+3}


\: \: \: \: \: \: \: \: \: \: \:


\: \: \: \: \: \: \: \: \:\tt{p(-1)=-6}

User Matt Mower
by
5.8k points